2006
DOI: 10.1063/1.2362930
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of band edge luminescence in ZnSe nanowires

Abstract: In order to realize the full potential of nanowires for optical applications, it is essential to synthesize nanowires that can emit predominantly via band to band or band edge (BE) transitions. However, many compound semiconductor nanowires, irrespective of the method of their growth, contain a high density of native defects; these result in competing deep defect (DD) related emission, limiting their utility for optoelectronic device applications. The concentration of these native defect states depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 20 publications
5
64
2
Order By: Relevance
“…Many works reported the defect-related emissions between 500 and 700 nm, such as point defect Zn vacancies, Zn interstitials, and structure defects dislocations, stacking faults and so on [35][36][37]. In the PL spectrum of Fe 3+ doped ZnSe nanoribbon, the narrow FWHM of D1 and D2 and the sharp near band-edge emission have eliminated the possibility of point defects for the latter often strongly relax the FX emission.…”
Section: Resultsmentioning
confidence: 99%
“…Many works reported the defect-related emissions between 500 and 700 nm, such as point defect Zn vacancies, Zn interstitials, and structure defects dislocations, stacking faults and so on [35][36][37]. In the PL spectrum of Fe 3+ doped ZnSe nanoribbon, the narrow FWHM of D1 and D2 and the sharp near band-edge emission have eliminated the possibility of point defects for the latter often strongly relax the FX emission.…”
Section: Resultsmentioning
confidence: 99%
“…This, however, can hinder the extrapolation of representative features as structural inhomogeneities may be present. There have been a number of investigations of PL emission from individual Ⅱ-Ⅳ NWs, mostly at room-temperature (RT) [7,[23][24][25][26][27][28]. However, many radiative states have a binding energy lower than RT, and thus cannot be seen [7].…”
Section: Introductionmentioning
confidence: 99%
“…The growth temperature for the sample was maintained at 650 • C. The nanowires have diameters in the range of 80-100 nm and lengths of 8-10 m. The nanowires were deposited on quartz substrates with a typical density of about 10 4 wires/mm 2 to perform the measurements reported in this work. Finally, we should point out that characterization of these samples can be found in detail elsewhere [5]. Photoluminescence measurements for the ZnSe nanowires grown under Se-rich and Zn-rich conditions are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the presence of the broad low energy luminescence peak is attributed to intrinsic point defects of the ZnSe lattice [4]. Recently, there has been a significant development in band edge emission control in this material [5]. It was demonstrated that nanowires grown under Zn-rich conditions are dominated by strong band edge emission, while nanowires grown under Se-rich conditions have strong defect-related emission.…”
Section: Introductionmentioning
confidence: 98%